Предмет: Алгебра,
автор: yooon80
(x+2) (x²-x-3)
-3(x+4)(x-1)
Помогите решить
Надо умножить многочлен на многочлен
Ответы
Автор ответа:
0
(x + 2)(x² - x - 3) = х³ - х² - 3х + 2х² - 2х - 6 = х³ + х² - 5х - 6
-3(x + 4)(x - 1) = -3(х² - х + 4х - 4) = -3(х² + 3х - 4) = -3х² - 9х + 12
Похожие вопросы
Предмет: Английский язык,
автор: dimasik777
Предмет: Английский язык,
автор: Snowflake2552
Предмет: Русский язык,
автор: Vladis77
Предмет: Математика,
автор: АружанВУНДЕРКИНД
Предмет: Математика,
автор: арина1071